Unpacking Receivables: Gresik Bottled Water Company’s Financial Analysis - Ariska Isnaini Putri; Anita Handayani (INNOVATION RESEARCH JOURNAL, 2023)
This research aims to identify and describe the causes of outstanding receivables and the handling efforts carried out by PT. XYZ, which is a bottled Drinking Water Company in Gresik Regency. The research method used is descriptive with a qualitative approach. The method used in this research process comes from interviews conducted with two selected informants and documentation of data on outstanding receivables for 2020-2022 at PT. XYZ. Data analysis techniques use Miles and Huberman. The findings from this research show that the factors causing outstanding receivables at PT. XYZ has 2 internal factors, namely lack of credit analysis, no special collection team, limited information, and external factors, namely intentional elements, economic conditions and customer environmental conditions. The resolution efforts carried out include monitoring, telephone information, warning letters, direct visits, judicial action, and implementing new policies.